2005
DOI: 10.1897/04-321r.1
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic fractionation indicates anaerobic monochlorobenzene biodegradation

Abstract: The concentration and isotopic composition of monochlorobenzene (MCB) was monitored in the plume of an anaerobic, contaminated aquifer in Bitterfeld, Germany. An enrichment in the carbon isotopic composition of more than 4 delta units was found at the fringes of the plume relative to the center (-26.5 %), suggesting the occurrence of in situ biodegradation of MCB. A similar enrichment was measured in a detailed cross-section of the plume and in depth-specific samples obtained in a multilevel sampling well. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 40 publications
1
48
1
Order By: Relevance
“…However, CB was shown to be degraded in situ at the fringe of the contaminant plume in an anoxic aquifer (with a long history of CB contamination) based on evidence from isotopic fractionation data and incorporation of [ 13 C]-labeled CB into long chain fatty acids of bacteria (Kaschl et al 2005;Kastner et al 2006).…”
Section: Anaerobic Degradation In the Environmentmentioning
confidence: 99%
“…However, CB was shown to be degraded in situ at the fringe of the contaminant plume in an anoxic aquifer (with a long history of CB contamination) based on evidence from isotopic fractionation data and incorporation of [ 13 C]-labeled CB into long chain fatty acids of bacteria (Kaschl et al 2005;Kastner et al 2006).…”
Section: Anaerobic Degradation In the Environmentmentioning
confidence: 99%
“…Yet, if contaminants undergo a preferential transport along the plumes and/or when biodegradation processes are taking place, the δ 13 C sum interpretation is not an easy task [31]. However, assuming that the carbon pool is conservative during anaerobic biodegradation (supposing DCBs → MCB → benzene) [32,33] and that aerobic processes are not inducing significant fractionations, particularly for CBs [23][24][25], δ 13 C sum values should retain their signature along the flowpath, regardless of the occurrence of degradation. Eventually, with further degradation and mineralization of benzene to CO 2 , δ 13 C sum could show an enrichment along the plume [32,33].…”
Section: Source Apportionmentmentioning
confidence: 99%
“…In contrast to compounds such as chlorinated ethenes, for which there is a well-developed literature on CSIA applications, only few studies are available for CBs. Significant carbon enrichment factors were obtained in laboratory experiments under anaerobic conditions, ranging from −0.8‰ to −6.3‰ for several CBs [22][23][24][25][26], which allows for the use of CSIA for tracing in situ biodegradation of CBs in contaminated anoxic aquifers. Kaschl et al [24,27] demonstrated MCB anaerobic biodegradation at two contaminated sites, while [28] investigated anaerobic biodegradation of dichlorobenzenes (DCBs) and MCB by interpreting CSIA results on the basis of an isotope mass balance approach.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations